1997
DOI: 10.1109/27.602505
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pulse shortening in high-power microwave sources

Abstract: Abstract-Observations show that the ubiquitous pulse shortening in high-power microwave (HPM) devices arises from the formation of plasma, electron streaming, high-E-field breakdown, and beam disruption. We review recent experiments in terms of these causes. Linear beam devices exhibit all of these mechanisms; in particular, beam disruption by E 2 B drifts in the strong microwave fields and diffusion in turbulent electric fields appear common. In relativistic magnetrons, the dominant effect is resonance destru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…1 The formation of electrode plasmas in these devices has been identified along with a shortening of the radiation pulse and other effects. [2][3][4][5][6][7][8] Through the use of electromagnetic (EM) particle-in-cell (PIC) simulation codes, device designs have been optimized for efficient power output 1 although these simulations have generally not been able to model measured impedance collapse or radiation cutoff. In the case of magnetically insulated line oscillators 9,10 (MILOs), long pulse operation (typically greater than $100 ns) is hampered, reducing the potential peak radiated energy from these devices.…”
mentioning
confidence: 99%
“…1 The formation of electrode plasmas in these devices has been identified along with a shortening of the radiation pulse and other effects. [2][3][4][5][6][7][8] Through the use of electromagnetic (EM) particle-in-cell (PIC) simulation codes, device designs have been optimized for efficient power output 1 although these simulations have generally not been able to model measured impedance collapse or radiation cutoff. In the case of magnetically insulated line oscillators 9,10 (MILOs), long pulse operation (typically greater than $100 ns) is hampered, reducing the potential peak radiated energy from these devices.…”
mentioning
confidence: 99%
“…For practical use, there is a trend to increase the hold-off voltage and maintain high vacuum sealed state for a long time [2]. Recently, in order to improve the vacuum condition, hybrid hard-tube technologies are introduced to traditional diodes by eliminating all plastic components and replacing o-ring seals with ceramic-metal welding [3]. However, because of vacuum flashover [4], the ceramic interface between liquid in pulse forming line (PFL) and vacuum always becomes the chock point of high power flow and it needs more consideration to the enhanced electric field around the triple junction (TJ) where ceramic, metal and vacuum are contiguous [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum gap breakdown becomes a hard problem which restricts the insulation and stability improvements of high-power vacuum electron devices. [1][2][3] Some researchers believed that electric field on microscopic surface and the field induced electron emission from electrode can be depressed by reducing the field enhancement factor of the microscopic protrusions on electrode surface, [4][5][6] so that the vacuum gap breakdown strength can be enhanced. Other researchers demonstrated that the breakdown strength of a vacuum gap was enhanced when the electrode roughness was reduced, but the limited enhancement was far less than the anticipation.…”
Section: Introductionmentioning
confidence: 99%